What if you have a humanoid AI robot doctor?: An investigation of public trust in South Korea. (2nd October 2022) - Kim, Do Kyun David; Kim, Sejin
ABSTRACT: Background: Humanoid robots with artificial intelligence have been implemented in many healthcare facilities including hospitals, nursing homes, and many others. Due to the development of technology and the increasing use of humanoid robots, it is expected that more advanced humanoid robots will be developed and implemented in healthcare facilities for better healthcare services. Based on this anticipation, this study proactively examined the public trust in humanoid AI robot (HAIR) doctors that we might have in the near future. Methods: This study employed two scales that have been predominantly used to measure patient-doctor trust through an extensive search across different scholarships. For data collection, online surveys were administered by posting a weblink to the online survey through social media, mostly Facebook, Twitter, and KakaoTalk, in South Korea. Results: Data analysis of 424 valid surveys found that the level of public trust in HAIR doctors as primary doctors was slightly higher than human doctors. For the data analysis using demographic variables, a series of t-test and ANOVA revealed that males showed a higher trust in HAIR doctors than females, while maintaining indifference in other demographic variables. Conclusion: Based on the rapid development of AI and robot technology, the implementation of HAIR doctors for our healthcare service would be a reality in the near future as the public also becomes more familiar with interacting with humanoid robots. Therefore, a proactive preparation for the future is urgently needed for effective use of future technology as well as patients' satisfaction.